COVID-19 clinical presentations: the modern mimic of other conditions - Mohamed Eltayieb Elawad; Abrar Bakry Elmalik; Doaa Mohamed Ahmed Hassan; Fatima Salaheldin Ibrahim Mohammed; Onaisa Hassan Kabroun Idris; Nasreen Sulaiman Omar Abdulaziz; Ibrahim A Ali (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2021)
The coronavirus pandemic (COVID-19) has placed enormous challenges on the health sector. Diagnosis is one of these challenges, where a clinical presentation may suggest a disease other than COVID-19. In this review we describe many presentations unrelated to the respiratory system. The ACE2 receptor is present in a wide variety of body tissues and it appears that this may be a link with the clinical pathology. To find these data we searched the major academic research engines, Google Scholar, and Pubmed, as well as the most recent case reports and original research published in specialized journals. An awareness of these uncommon presentations helps health workers to recognize and treat the disease early and appropriately.